Abu Samah Mohd. Kassim pejuang kiri kemerdekaan zuriat Datuk Bahaman - Mohamed Salleh Lamry (Strategic Information and Research Development Centre, 2008)
Biography of Abu Samah bin Muhamad Kasim, Malaysian Muslim communist and political activist joining the Malayan Communist Party.